Reformulasi Ketentuan Sanksi Perkosaan Dalam Perkawinan Berdasarkan Perspektif Feminist Legal Theory - Sudiarto; Hirsanuddin; Chrisdianto Eko Purnomo (Faculty of Law, University of Mataram, 2025)
This study aims to analyze the occurrence of unilateral execution auctions for collateral, the procedures and implementation of execution auctions, and the legal protection for customers for execution auctions for collateral. The method used in this study is the statute approach, the conceptual approach. Data collection techniques include document study techniques, observation, and interview techniques. These factors cause unilateral execution auctions because one party defaults on the agreed agreement. The factors that cause default are divided into two, namely, the first internal factor and the external factor. The Mortgage Execution Auction procedure consists of 3 procedures: the Pre-Auction Procedure, the Auction Implementation Procedure, and the Auction Minutes. That legal protection is divided into repressive legal protection and preventive legal protection. In implementing the execution auction of the Mortgage Right collateral object, the Bank has not protected customers. When the KPKNL has approved an auction application for a collateral object of a Mortgage Right, the Bank makes an auction announcement and is late in notifying the customer that the collateral object of the Mortgage Right will be auctioned, the customer can obtain legal protection against losses received from the sale of the Mortgage Right that he owns at a price that is far from the fair and reasonable value.